**Let:**

YES = Real Yesterday

YES’ = Imaginary Yesterday

TOD = Real Today

TOD’ = Imaginary Today

TOM = Real Tomorrow

TOM’ = Imaginary Tomorrow

**Assumption I:**

**1.** Yesterday in the sentence is the **Real Yesterday (YES)**.

**2.** Tomorrow in the sentence is the **Imaginary Tomorrow (TOM’)**.

**3.** Today in the sentence is the **Imaginary Today (TOD’)**.

**Thus:**

**YES = TOM’** *(i)*

**TOD’ = Friday** *(ii)*

**TOM’ = TOD’ + 1** *(iii)*

**TOD = YES + 1** *(iv)*

**Using equation ***(i)* and *(iii)*:

YES = TOM’

YES = **(TOD’ + 1)**

**YES = TOD’ + 1** *(v)*

**Using equation ***(iv)* and *(v)*:

TOD = YES + 1

TOD = **(TOD’ + 1)** + 1

**TOD = TOD’ + 2** *(vi)*

**Using equation ***(ii)* and *(vi)*:

TOD = TOD’ + 2

TOD = **Friday** + 2

**TOD = Sunday**

**Assumption II:**

**1.** Yesterday in the sentence is the **Imaginary Yesterday (YES’)**.

**2.** Tomorrow in the sentence is the **Real Tomorrow (TOM)**.

**3.** Today in the sentence is the **Imaginary Today (TOD’)**.

**Thus:**

YES’ = TOM

A**TOM = YES’** *(i)*

**TOD’ = Friday** *(ii)*

**YES’ = TOD’ – 1** *(iii)*

**TOD = TOM – 1** *(iv)*

**Using equation ***(i)* and *(iii)*:

TOM = YES’

TOM = **(TOD’ – 1)**

**TOM = TOD’ – 1** *(v)*

**Using equation ***(iv)* and *(v)*:

TOD = TOM – 1

TOD = **(TOD’ – 1)** – 1

**TOD = TOD’ – 2** *(vi)*

**Using equation ***(ii)* and *(vi)*:

TOD = TOD’ – 2

TOD = **Friday** – 2

**TOD = Wednesday**

Q.E.D.

[collapse]